Análise dinâmica e cálculo da fadiga de estruturas de plataformas marítimas - Oliveira, Albert Martins de (1985)
The main purpose of this work is to study the dynamic behaviour and the change in the fatigue damage corresponding to fixed offshore steel structures when there are changes in analysis parameters. The dynamic behaviour for structures similar to those of real offshore platforms is determined using the Finit Element Method, by means of computer programs for dynamic response in the time and in frequency domain, available at Petrobras, as part of the Computational System ADEP. The fatigue damage is obtained using the computer subsystem for deterministic fatigue analysis called FADES, wich is also a part of the ADEP System.